Patient Satisfaction and Its Socio-Demographic Correlates in a Tertiary Hospital of Nepal - Banstola, Bidhya (Journal of Nepal Health Research Council, 2024)
Background: Patient satisfaction is an integral component of patient care. This concept has been already integrated in the developed nations and the topic is getting interest in developing nations. Hence attempt has been made to address the satisfaction of the patients in different settings and hospitals. The objective of this study was to assess the satisfaction and likely sociodemographic factors affecting the satisfaction among the outpatients.Methods: A cross-sectional study was conducted among 207 outpatients visiting different departments of the hospital by systematic random sampling method. The satisfaction was assessed by the abbreviated form of Patient Satisfaction Questionnaire-18 and the mean scores of seven domains were obtained. Results: Mean satisfaction level was 3.53(0.40) out of 5. Highest level of satisfaction was in interpersonal manner domain and the lowest in accessibility and convenience domain. None of the sociodemographic variables was significantly associated with the overall satisfaction (p>0.05). Enrollment into the national health insurance, occupation and educational status of the patients were found to significantly affect one or more domains. Conclusions: This study showed that the overall satisfaction was fair; hence there is room for improvement for better patient satisfaction. Hospital needs to focus on easy accessibility and convenience of the healthcare facilities and resources to the patients.Keywords: Nepal; patient satisfaction; socio-demographic tertiary hospital.